METHOD FOR DEVELOPMENT MODELS OF POLYSUBJECT MULTIFACTOR ENVIRONMENT OF SOFTWARE COMPLEX’S SUPPORT - Pukach, A. I; Teslyuk, V. M (Radio Electronics, Computer Science, Control, 2025)
Context. The task of development the models of a polysubject multifactor environment for software’s complex support is considered in this research, that ensures possibilities of taking into account the influence of various impact factors onto the supported software complexes themselves, onto their complex support’s processes, as well as onto the subjects (interacting with them) who provide and implement this complex support. The object of study are the processes of complex support of software products, the processes of automation of this complex support, the processes of influence of impact factors onto the object and subjects of the complex support of software products, as well as the processes of perception’s subjectivization of the supported object by relevant subjects of interaction with it. The subject of study are methods and means of artificial neural networks, in particular a multilayer perceptron, as well as a computer design and modeling. Objective is the development of the method for building models of a polysubject multifactor environment(s) of the complex support of software product(s). Method. The developed method for building models of a polysubject multifactor environment of software complexes’ support is proposed, which makes it possible (in an automated mode) to obtain appropriate models, based on which, later on – to investigate the strengths and weaknesses of a specific researched complex support’s environment(s) of a particular investigated software product(s), in order to ensure further improvement and automation of this complex support based on the study and analysis of impact factors, which form the subjective vision and perception of this complex support by those subjects who directly provide and perform it, that is, in fact, on whom this support itself depends, as well as its corresponding qualitative and quantitative characteristics and indicators. Results. The results of functioning of the developed method are corresponding models of investigated polysubject multifactor environments of the complex support of software products, which take into account the presence and the level of influence of relevant existing and present factors performing impact onto the subjects of interaction with supported software complexes, which (subjects) directly provide and perform the complex support for the studied software products, and also form relevant researched support environments. In addition, as an example of a practical application and approbation, the developed method was used, in particular, to solve the applied practical task of determining the dominant and the deficient factors of influence of a polysubject multifactor environment of the studied software complex’s support, with presenting and analyzing the obtained results of resolving the given task. Conclusions. The developed method resolves the problem of building models of a polysubject multifactor environment of the complex support of software products, and ensures taking into account the action of various impact factors performing influence onto the supported software complex itself, onto the processes of its support, as well as onto the subjects of interaction with it, which (subjects) provide and perform this complex support. In particular, the developed method provides possibilities for modeling and investigating a polysubject multifactor environments of the “in focus” software product’s complex support, which reflect the global (or the local, it depends on the specific tasks) impact of various existing factors making influence onto the object of support itself (the supported software complex, or the processes of its complex support), as well as onto the subjects which directly carry out and implement this complex support in all its possible and/or declared manifestations. The practical approbation of the developed method has been carried out by solving specific applied practical tasks, one of which is presented, as an example, in this paper, – which is the task of determining the dominant and the deficient factors of influence of a polysubject multifactor environment of the studied software complex’s support, and this approbation, actually, confirms its effectiveness in solving a stack of applied practical problems related to researching the impact of factors performing influence onto the complex support of software products, using the advantages of artificial intelligence technologies, machine learning, artificial neural networks, and multilayer perceptron in particular